NIEWAŻNOŚĆ ZRZECZENIA SIĘ PRZEZ POLSKĘ REPARACJI WOJENNYCH A NIEMIECKIE ROSZCZENIA ODSZKODOWAWCZE - Sandorski, Jan (Wydział Prawa i Administracji UAM, 2004)
It has become a bad tradition in the Polish-German relations that from time to time the problem of war reparations and claims for indemnity for the consequences of the Second World War is brought back. It is beyond all doubt that after 1989 neither the Polish diplomacy nor the theory of international law reacted to the fact that the problem of the assumption of German property by Poland after the Second World War was now in a different political context. Western superpowers signed treaties in which they shifted the obligation to pay indemnities to German citizens in connection with war reparations onto the German state. Poland has not managed to negotiate similar regulations with the Federal Republic of Germany. In the present situation, the so-called “treaty path” seems to be the most reasonable solution. It would refer to Józef Pilsudski’s policy, who led to the conclusion of the liquidation agreement between Poland and Germany on 31 October, 1929. After the “zero” effect has been reached in the negotiations with the Federal Republic of Germany the indemnity obligations would be shifted onto the German side in exchange for Polish waiver of war reparations. The question arises whether Poland has the right for them, considering the fact that it relinquished them in 1953. The declaration of the Polish government of 23 August, 1953 was a result of the Soviet dictate, which violated sovereignty of Poland and as a result of which the government of the Polish People’s Republic was not an equal partner for international relations. For that reason, it must be stated that there are serious premises indicating the thesis of invalidity of declaration of 23 August, 1953. The declaration of the government of the Polish People’s Republic of 23 April, 1953 is burdened with a defect in a declaration of will and, due to that, there is no need to withdraw it. The international law does not set any time limit within which an invalidity charge must be submitted. For that reason, the charge may be notified if the need arises. Submitting an invalidity charge of the declaration of 1953 is not equivalent to accepting a thesis about limiting Polish sovereignty during its membership in the Communist block. From the point of view of international law, in the aforementioned period Poland was a sovereign entity. Its home and foreign policy was under a strong political influence of the Soviet Union, which did not change its position in the international law. More than once this influence was clearly against the international law in force, so it was a violation of Polish sovereignty. For this reason, the declaration of 23 August, 1953 should be considered invalid and lacking legal consequences.
INVALIDITY OF POLISH WAIVER OF WAR REPARATIONS VS. GERMAN CLAIMS FOR INDEMNITY